Size, concentration, and origin of human exhaled particles and their dependence on human factors with implications on infection transmission. (February 2023) - Bagheri, Gholamhossein; Schlenczek, Oliver; Turco, Laura; Thiede, Birte; Stieger, Katja; Kosub, Jana M.; Clauberg, Sigrid; Pöhlker, Mira L.; Pöhlker, Christopher; Moláček, Jan; Scheithauer, Simone; Bodenschatz, Eberhard
Abstract: Understanding infection transmission between individuals, as well as evaluating the efficacy of protective measures, are key issues in pandemics driven by human respiratory particles. The key is a quantitative understanding of the size and concentration of particles exhaled and their variability across the size range for a representative population of all ages, genders, and different activities. Here we present data from 132 healthy volunteers aged 5 to 80 years, measured over the entire particle size range for each individual. Conventional particle spectrometry was combined with in-line holography under well-controlled conditions for common activities such as breathing, speaking, singing, and shouting. We find age to be the most important parameter for the concentration of small exhale particles <5 µm (PM5), which doubles over a 7-year period in adolescents and over a 30-year period in adults. Gender, body mass index, smoking or exercise habits have no discernible effect. We provide evidence that particles with a diameter of <5 µm originate from the lower respiratory tract, 5–15 µm from the larynx/pharynx, and >15 µm from the oral cavity. PM5 concentration can vary by one order of magnitude within a person, while inter-person variability can span two orders of magnitude, largely explained by difference in age. We found no discernible inter-person variability for particles larger than 5 µm. Our results show that cumulative volume of PM5 is 2–8 times higher in adults than in children. In contrast, number and volume concentration of larger particles, which are produced predominantly in the upper respiratory tract, is largely independent of age. Finally, we examined different types of airborne-transmissible respiratory diseases and provided insights into possible modes of infection transmission with and without several types/fits of face masks. Highlights: Measurement of particles in the air exhaled by 132 persons aged 5–80 years. Aerosol spectrometry and in-line holography used to measure nm to mm range. Breathing produces mainly <5 μ m, while vocalizations have a second peak at ∼ 38 μ m. Biological age is important for particles <5 μ m, gender and BMI have no impact. <5 μ m originate from lungs, 5–15 μ m from larynx/throat, >15 μ m from oral cavity.